# Answer to Question #1864 in Calculus for Abhilash

Question #1864

Find the number c that satisfies the conclusion of the Mean Value Theorem.

f(x) = 3x^2 + 2x + 1

[-1, 1]

f(x) = 3x^2 + 2x + 1

[-1, 1]

Expert's answer

According to the& Mean Value Theorem,

f'(c) = (f(b) - f(a))/(b-a) = (f(1) - f(-1))/(1-(-1)) = 4/2 = 2

f'(c) = 6c + 2 = 2

c = 0

f'(c) = (f(b) - f(a))/(b-a) = (f(1) - f(-1))/(1-(-1)) = 4/2 = 2

f'(c) = 6c + 2 = 2

c = 0

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment